Keluarga Nelayan dan Budaya Sibaliparri’: Menyingkap Relasi Kesetaraan Gender dalam Masyarakat Mandar - Mahyuddin Mahyuddin; Muh. Wahyuddin; Wahyuni Wahyuni (AL-MAIYYAH : Media Transformasi Gender dalam Paradigma Sosial Keagamaan, 2020)
This study aims to explain the relation of gender equality in distributing of role between man and woman in the cultural Siballiparri’ of fishing families in Mandar community. This type research is a qualitative decriptive which takes place in Campalagian, Polewali Mandar West Sulawesi Indonesia. Data collection techniques are observation, in-depth interviews, and documentation. The results of this study indicate that there were mutual awareness between the husband and wife where they develop mutual understanding, sympathy, respect and help each other in fulfilling the need of their family life. Siballiparri’ is understood and created on the basis of an agreement, partnership or equality, between men and women to meet the economic needs of a household. They understand their roles and responsibilities regarding both material and spiritual needs for the unity of a household.